Characterization and expression profile analysis of the 3‐phosphoglycerate dehydrogenase family in rice. (7th March 2021) - Wang, Baoxiang; Guo, Tao; Wang, Haifeng; Li, Jingfang; Sun, Zhiguang; Liu, Yan; Xing, Yungao; Xu, Bo; Yang, Bo; Li, Jian; Chi, Ming; Liu, Jinbo; et al.
Abstract: The plastidial 3‐phosphoglycerate (3‐PGA) pathway plays an important role in supplying serine in non‐photosynthetic tissues in plants under environmental stresses. Synthesis of serine in rice ( Oryza sativa L.) is intangible, but little kinetic and structural information for enzymes is available. In this study, a comprehensive characterization and analysis of phylogenetic variable was carried out on three 3‐phosphoglycerate dehydrogenase (PGDH) members in rice, in addition to an analysis of their whole‐life expression patterns. All of the O ryza sativa phosphoglycerate dehydrogenases ( OsPGDHs ) have three highly conserved motifs. The three genes were detected in all tissues and development stages in ( Oryza sativa, ssp. japonica Nipponbare) by quatitative real‐time polymerase chain reaction (qRT‐PCR). Under abiotic stresses, such as salt, drought, oxidative and low temperature, the expressions of all these OsPGDHs were significantly altered. These results highlighted the importance of the OsPGDH family in phosphorylated serine biosynthesis pathway in rice. Core Ideas: The phosphoglycerate dehydrogenase genes are responsible for serine synthesis. The expression patterns of three different rice phosphoglycerate dehydrogenase genes differed by tissue type and stress. Expression of Oryza sativa phosphoglycerate dehydrogenase genes is influenced by abiotic stresses.